Joint Property Distribution upon Divorce Reviewed From the Contribution of Husband and Wife in the Household - Ristianawati, Eka (Universitas Islam Negeri Walisongo Semarang, 2021)
Joint property distribution has been regulated in the Islamic Law Compilation (KHI), namely, Article 97 which explains that a widow or widower is entitled to half of the joint property. The distribution is fair if the husband and wife make the same contribution in the marriage. However, in fact, today we often find that wives are being the backbone of the family while husbands do not earn a living or husbands earn a living for the family, but wives do not take care of the household. If such a situation is found, is the article 97 of KHI still relevant? This paper presents a concept of joint property distribution based on the contribution of husband and wife in marriage which is considered fairer for both of them than what has been stipulated in the KHI and the Civil Code Articles 128-129. The type of research used is descriptive research. This means that research is discussed in the form of an explanation described in words carefully and thoroughly. The approach method used in this research is a normative juridical approach. The results of this study explain that to obtain the justice, judges can act contra legem (against the law) where justice should give a share to everyone based on his services or contributions (Aristotle). The joint property distribution in marriage from a justice perspective is the distribution of joint property by assessing the amount of contribution of the parties. A fair share does not have to be 50% for widowers and 50% for widows. The husband can get a smaller share from the wife if the contribution is less during the marriage and does not carry out his obligation as the breadwinner and the wife can get a larger share from the husband if the wife plays a dual role, and vice versa.Pembagian harta bersama telah diatur dalam Kompilasi Hukum Islam yakni pada pasal 97 dijelaskan bahwa janda atau duda berhak separuh dari harta bersama. Pembagian tersebut adil apabila suami dan istri memberikan kontribusi yang sama dalam perkawinan. Akan tetapi pada faktanya saat ini sering kita temui istri menjadi tulang punggung keluarga sedangkan suami tidak mencari nafkah atau suami mencari nafkah untuk keluarga akan tetapi istri tidak mengurus rumah tangga. Jika ditemukan keadaan seperti itu apakah masih relevan KHI pasal 97 tersebut. Tulisan ini menyajikan sebuah konsep pembagian harta bersama berdasarkan kontribusi suami istri dalam perkawinan yang dinilai lebih adil untuk keduanya daripada apa yang sudah diatur dalam KHI dan KUHPerdata Pasal 128-129. Hasil dari penelitian ini dijelaskan bahwa untuk mendapatkan sebuah keadilan hakim dapat bertindak contra legem (mengenyampingkan undang-undang) dimana keadilan itu seharusnya memberikan bagian kepada setiap orang didasarkan atas jasa-jasanya atau kontribusinya (aristoteles). Pembagian harta bersama dalam perkawinan jika dilihat dari perspektif keadilan adalah pembagian harta bersama dengan menilai besaran konstribusi para pihak. Dimana pembagian yang adil tidak harus 50 % untuk duda dan 50% untuk janda. suami bisa mendapatkan bagian yang lebih kecil dari istri apabila kontribusinya kurang selama perkawinan dan tidak menjalankan kewaibannya sebagai pencari nafkah dan istri bisa mendapatkan bagian yang lebih besar dari suami jika istri berperan ganda, begitu uga sebaliknya.